Pengaruh Pengerasan Beton Menggunakan Superplasticizer Terhadap Kuat beton Busa - M Royan Firdaus; Sartika Nisumanti; Khodijah Al Qubro (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
ABSTRACT A new product of lightweight concrete that has a low specific gravity that is increasingly used in the world of construction is foam concrete. In this study, testing the addition of superplasticizers to the foam concrete mixture was carried out, by analyzing the effect of adding superplasticizers as much as 0.3% of the amount of cement on the process of setting time and compressive strength of foam concrete. The purpose of the study was to determine the effect of adding superplasticizers as much as 0.3% of the amount of cement on the process setting time and compressive strength of foam concrete. In this study, the method used was an experimental method. The results showed that the addition of superplasticizers to the concrete mixture can make the cement binding time longer than without the addition of superplasticizers to the concrete mixture. While in testing the compressive strength of concrete, there is a significant increase in concrete strength in concrete variations with the addition of superplasticizers, this is because the use of added superplasticizers can reduce water use so that the cement water factor becomes lower and improves concrete quality. Keywords: Concrete Foam, Superplasticizer, Compressive Strength ABSTRAK Produk baru beton ringan yang mempunyai berat jenis rendah yang semakin banyak digunakan dalam dunia konstruksi yakni beton busa. Pada penelitian ini dilakukan pengujian penambahan superplasticizer pada campuran beton busa, dengan menganalisis pengaruh penambahan superplasticizer sebanyak 0,3% dari jumlah semen terhadap proses setting time dan kuat tekan beton busa. Dengan tujuan penelitian adalah untuk mengatahui pengaruh penambahan superplasticizer sebanyak 0,3% dari jumlah semen terhadap proses setting time dan kuat tekan beton busa. Dalam penelitian ini metode yang digunakan adalah metode eksperimental. Hasil penelitian menunjukan dengan adanya penambahan superplasticizer kedalam campuran beton dapat membuat waktu ikat semen lebih lama dibandingkan tanpa penambahan superplasticizer kedalam campuran beton. Sedangkan pada pengujian kuat tekan beton terjadi peningkatan kekuatan beton secara signifikan pada variasi beton dengan penambahan superplasticizer, hal tersebut dikarenakan penggunaan bahan tambah superplasticizer dapat mengurangi pemakaian air sehingga faktor air semen menjadi lebih rendah dan meningkatkan mutu beton. Kata kunci: Beton Busa, Superplasticizer, Kuat Tekan